2018
DOI: 10.1007/jhep08(2018)143
|View full text |Cite
|
Sign up to set email alerts
|

Infinite distances in field space and massless towers of states

Abstract: It has been conjectured that in theories consistent with quantum gravity infinite distances in field space coincide with an infinite tower of states becoming massless exponentially fast in the proper field distance. The complex-structure moduli space of Calabi-Yau manifolds is a good testing ground for this conjecture since it is known to encode quantum gravity physics. We study infinite distances in this setting and present new evidence for the above conjecture. Points in moduli space which are at infinite pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

52
802
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(854 citation statements)
references
References 92 publications
(240 reference statements)
52
802
0
Order By: Relevance
“…If it is a pseudo‐scalar like an axion, it can avoid fifth‐force constraints, but a typical axion potential is flat enough to drive a period of accelerated expansion only if its decay constant is trans‐Planckian . This is in disagreement with recent studies of axion field ranges from string theory . On the other hand, if the quintessence field is a scalar, it is not clear how to avoid the existing stringent bounds from fifth‐forces .…”
Section: Quintessence In String Theorymentioning
confidence: 77%
See 1 more Smart Citation
“…If it is a pseudo‐scalar like an axion, it can avoid fifth‐force constraints, but a typical axion potential is flat enough to drive a period of accelerated expansion only if its decay constant is trans‐Planckian . This is in disagreement with recent studies of axion field ranges from string theory . On the other hand, if the quintessence field is a scalar, it is not clear how to avoid the existing stringent bounds from fifth‐forces .…”
Section: Quintessence In String Theorymentioning
confidence: 77%
“…In order to perform a proper study of the implications for quintessence, they have to be considered within a full moduli stabilisation mechanism. However, as mentioned above, one generically needs trans‐Planckian axionic decay constants to drive a period of accelerated expansion while recent studies of axion field ranges in string theory showed that this is very hard to achieve …”
Section: Quintessence In String Theorymentioning
confidence: 99%
“…Note that this shows that the Weak Gravity Conjecture is really a statement about non‐perturbative quantum gravity, it is violated in perturbative string theory. Studies of the Weak Gravity Conjecture in the context of closed‐string U (1)s were made in []. Note that some of these can also be considered studies of open‐string U (1)s, as considered in section 4.5.2, because at strong coupling the distinction becomes rather blurred.…”
Section: Swampland Tests In String Theorymentioning
confidence: 99%
“…Already for N=2 the spectrum of half‐BPS states in the theory (supersymmetric wrapped branes) depends on the position in moduli space. However, we will utilize a useful and general technique in section 4.7 that will allow to identify such a tower even for complicated geometries . The physics of it will actually play an important role throughout much of this review and so it is worth discussing in this simple setting first.…”
Section: Swampland Tests In String Theorymentioning
confidence: 99%
“…In [] the authors also point out an interesting connection between their refined dS swampland conjecture and the swampland distance conjecture . They do so by using Bousso's covariant entropy bound and thereby provide support for their refined dS swampland conjecture in the asymptotic regime, which is parametrically controlled in a strict, mathematical sense.…”
Section: Introductionmentioning
confidence: 98%